From the arid ground up - Stevensson, Linn (2015)
This thesis explores constructed water landscapes and the attitudes creating them in the Salton Sea area, which is located in the converge of the Mojave and the Sonoran Deserts in southeast California. With the focus on water constructions the thesis embraces the method of the Deviant Transect, under development by the landscape architect researchers Gini Lee and Lisa Diedrich, with Ellen Braae. The method aims at enabling designers to capture qualities that can only be perceived on site, such as dynamics, relationships and atmospheres, in order to support site-specific transformation of sites. This thesis challenges Antropocentrism, inspired by writings of Dirk Sijmons (2014) and Saskia Sassen (2014). Amongst others, Carol J. Burns and Andrea Kahn’s (2005) theories on site and site specificity, are studied, along with literature on grass root movements and societal change suggested by Grace Lee Boggs (2011) . This work examines water constructions in the Salton Sea area, acknowledging them in two ways: as land colonization with themes such as water systems, industrial scaled farming, and sub-urban settlements, and as oppositions to conventional land use practices, with themes of the desert as a garden, local food, and the culture of mobile homes. The resulting findings are the basis for a design proposal that acknowledges what is already in place by introducing a network of test sites. The aim is to use landscape architectural skills in order to engage in a speculative form of regional design, enabling visionary organizing rather than providing finished blueprints.